Euroization: What Factors drive its Persistence? - Helmut Stix (Oesterreichische Nationalbank (OeNB), 2008)
The question asked in this paper is why people continue to use foreign currencies even after their economies have stabilized. Survey data for Croatia, Slovenia and Slovakia are employed to provide an answer. The results confirm the role of network effects and of remittances. Furthermore, the extent of currency substitution is found to be positively associated with the level of income and education. An important aspect of euroization seems to be age (the older are more likely to hold foreign currencies). In contrast, neither expectations about inflation rates, nor about exchange rates, do seem to affect the degree of euroization in a systematic and predictable way. Trust in the banking system is found to affect the choice between foreign currency cash and foreign currency deposits. Overall, the results support the view that the persistence in the use of foreign currencies is driven to a large extent by factors that are related to the past.
Keywords: E41; E50; D14; 330; Dollarization; euroization; currency substitution; survey data